Kahoot-Based Learning and Students’ Critical Thinking in Islamic Education - Lusi Khairani; Meyniar Albina (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The integration of digital learning media has become essential in modern education to enhance student engagement and higher-order thinking skills. Specific Background: In Islamic Religious Education (PAI), students’ critical thinking abilities often remain low due to conventional lecture-based approaches, as observed at SMP IT Nurul Ilmi Medan. Knowledge Gap: Although previous studies highlight the benefits of game-based learning platforms such as Kahoot, limited research explores how its implementation specifically shapes learning processes, teacher strategies, and students’ critical thinking skills within PAI classrooms. Aims: This study investigates the implementation of Kahoot in PAI learning and examines its role in improving students’ critical thinking abilities. Results: Findings show that Kahoot increases student participation, creates an enjoyable and interactive learning atmosphere, and enhances analytical, evaluative, and reflective thinking as evidenced by improved learning engagement and performance. Supporting factors include school Wi-Fi, teacher readiness, and student motivation, while inhibiting factors involve device limitations and unstable internet access. Novelty: This study provides an in-depth qualitative analysis of Kahoot’s pedagogical integration, moving beyond outcome evaluation to examine learning dynamics and contextual challenges. Implications: Kahoot serves as an effective digital strategy to foster critical thinking in PAI learning and supports the principles of 21st-century education and the Pancasila Student Profile. Highlights: Kahoot improves student engagement and strengthens critical thinking in PAI learning. Implementation success depends on teacher readiness, supportive infrastructure, and meaningful question design. Game-based learning offers an effective strategy aligned with 21st-century education demands. Keywords: Kahoot, Islamic Education, Critical Thinking, Digital Learning, Gamification